Impact of Social Media Marketing on Small Businesses’ Sales Performance: A Case of Women Clothing Stores in Nyamagana District, Tanzania - Silvano, Glory; Mbogo, Crispin (International journal of Engineering, Business and Management, 2022)
This study was conducted toinvestigate the impact of Social Media Marketing on Small Businesses’ Sales Performance: A Case of Women Clothing Stores in Nyamagana District, Tanzania. The study used quantitative research approach. Data was collected through questionnaires, and the analysis was conducted using quantitative means by which statistical package for social science (SPSS V 22) software was employed quantitative analysis was employed.ANOVA was applied to predict how use Facebook, Instagram and Twitter for marketing purposes influences the sales performance of small businesses engaging in women clothing retailing.In this study,regression analysis was applied to find out the relationship equation for the independent variable (use of Facebook, Instagram, and Twitter).Through this the researcher was able to understand the effects of the relationship between independent variable and dependent variable of the study. The result obtained through regression analysis established that Facebook has impacts on the sales performance of small business (Beta = .199, P <.020). The results obtained in this aspect shows that the increase in the use of Facebook by 1 unit attributes increase of performance of small business by 0.20. On Instagram, thefindings obtained through linear regression established that Instagram has a significant impact on the sales performance of small business (Beta = .369, P <.947). And on Twitterthe results obtained through regression analysis revealed that Twitter has no direct relationship on the sales performance of small business (Beta = -.599, P <-.945). The study recommends further studies to be conducted on the strategies to be used to improve the application of social media in the small business.